Properties of granite derived residual soils / Mohamad Ismail Kepli - Kepli, Mohamad Ismail (1994)
This research project is aimed to study the properties of granite derived residual soils. The samples were taken from two sites in Melaka, Good result expected to be obtained because the samples collected are undisturbed. The samples nicely bored and great care taken to transport the samples from Melaka. Disturbed samples mainly were used in performed the classification tests. Whereas the undisturbed samples prepared for strength tests. The results were compared to existing granitic residual soils properties taken from skepper et al, Yee and Ooi, etc. The results obtained are in intermediate correlation to them. Malaysia is rapidly developing countries, demand bigger and high rise structures. These situations brought about a general awareness of the soil problems amongst engineers. To understand better the problems, it is necessary to know the soil distributions and their engineering properties.